The effect of polymer matrices on the thermal hazard properties of RDX-based PBXs by using model-free and combined kinetic analysis - Yan, Qi-Long; Zeman, Svatopluk; Sánchez Jiménez, P E; Zhao, Feng-Qi; Pérez-Maqueda, L A; Málek, Jiří (Journal of hazardous materials, 2014)
In this paper, the decomposition reaction models and thermal hazard properties of 1,3,5-trinitro-1,3,5-triazinane (RDX) and its PBXs bonded by Formex P1, Semtex 1A, C4, Viton A and Fluorel polymer matrices have been investigated based on isoconversional and combined kinetic analysis methods. The established kinetic triplets are used to predict the constant decomposition rate temperature profiles, the critical radius for thermal explosion and isothermal behavior at a temperature of 82°C. It has been found that the effect of the polymer matrices on the decomposition mechanism of RDX is significant resulting in very different reaction models. The Formex P1, Semtex and C4 could make decomposition process of RDX follow a phase boundary controlled reaction mechanism, whereas the Viton A and Fluorel make its reaction model shifts to a two dimensional Avrami-Erofeev nucleation and growth model. According to isothermal simulations, the threshold cook-off time until loss of functionality at 82°C for RDX-C4 and RDX-FM is less than 500 days, while it is more than 700 days for the others. Unlike simulated isothermal curves, when considering the charge properties and heat of decomposition, RDX-FM and RDX-C4 are better than RDX-SE in storage safety at arbitrary surrounding temperature.
Keywords: exploze; triaziny; Triazines; Explosions; teplota; výbušné látky; Models, Theoretical; Polymers; kinetika; Explosive Agents; Temperature; teoretické modely; Kinetics; polymery